At home parent-administered dressing changes in paediatric burns aftercare: A survey of burns centres?" practice. Issue 2 (March 2022) - Thompson, Dean M; Thomas, Clare; Hyde, Lisa; Wilson, Yvonne; Moiemen, Naiem; Mathers, Jonathan
Highlights: Most UK paediatric burns services support parent-administered dressings changes. Parent-administered dressings reduces familial financial and educational burden. No services report formal eligibility criteria for parent-administered dressings. Abstract: Objective: Following paediatric burn injury, dressings are initially changed in outpatient clinics, necessitating regular visits with substantial burden for parents, children and services. This can potentially be lessened if some parents go on to administer dressing changes for their child at home. However, a lack of data regarding support for parent-administered dressing changes is present. The aim of this study was to describe current practice and views regarding at-home parent-administered dressing changes (PAD) in the UK. Methods: An online survey was distributed to 20 paediatric burns services in England and Wales. The survey used fixed and free-text responses to collect data on whether PAD is offered and the reasons for this; patient and parent eligibility criteria; training and support; and respondents?" views on the advantages and disadvantages of PAD. Analysis comprised simple descriptive statistics and simple content analysis of free-text responses. Results: Thirteen responses were received (response rate = 65%). Eleven respondents indicated their service offers PAD. Two respondents reported their service does not offer PAD due to alternative nurse outreach appointments (n = 1), and service resource limitations (n = 1), though another respondent indicated service cost savings. Twelve respondents regard PAD positively (n = 8) or very positively (n = 4). Most respondents reported that 10% or fewer parents refuse PAD when offered (n = 7). Perceived advantages of PAD included reduced travel burden (n = 9), patient better able to cope with dressing changes (n = 8), better school and work attendance for child and parent respectively (n = 6), and reduced financial impact on families (n = 4). No formal eligibility criteria for PAD are extant, though 5 respondents described informal criteria in place in their service, predominantly involving dressing frequency (n = 5), and size or complexity of wound (n = 4). Conclusion: The survey indicates that most paediatric burns services support PAD. However, the absence of formal eligibility criteria, and informal criteria open to interpretation, risks inequity of support received by children and their families. Further research should evaluate whether this inequity extends to variable clinical outcomes to determine what works for who and under what circumstances when supporting parents in paediatric burns aftercare.